Local coral connections within an atoll reef system underlie reef resilience and persistence - Camille M. Grimaldi; Cal Faubel; Luke Thomas; Ayse D. Sahin; Nicole M. Ryan; Matt Rayson; Rebecca Green; Michael W. Cuttler; Eric A. Treml; Ryan. J. Lowe; James P. Gilmour (Limnology and Oceanography, 2024)
The recovery of isolated reef systems is a complex process that is usually associated with the supply of coral larvae from distant reefs (or large‐scale connectivity). However, a frequently neglected process is the potential for supply within the reef itself (or local connectivity). In this study, we quantify and characterize the role of local connectivity over 21 yr of simulated annual coral spawning on an isolated coral reef atoll using outputs from a high‐resolution biophysical model ( 100 s km) and is exported away from the system. Local dispersal plays a pivotal role in creating a highly‐connected network across the reef, enhancing exchanges of larvae within the same reef patches (local retention), across reef zones (e.g., lagoon, reef flat), and across the larger reef system. Finally, we show that this highly‐connected network exhibits a certain level of robustness, even when exposed to environmental stressors such as thermal‐induced mortality. Our findings highlight the previously overlooked role of local scale dispersal in driving recovery of isolated reef systems and emphasize the importance of targeted local management actions, indicating that efforts directed at enhancing and preserving local connectivity can have a substantial impact on the overall health and resilience of isolated reef ecosystems.